On the Derivation of Exact Solutions of a Tapered Cantilever Timoshenko Beam - Foek Tjong Wong; Junius Gunawan; Kevin Agusta; Herryanto Herryanto; Levin Sergio Tanaya (Institute of Research and Community Outreach - Petra Christian University, 2019)
A tapered beam is a beam that has a linearly varying cross section. This paper presents an analytical derivation of the solutions to bending of a symmetric tapered cantilever Timoshenko beam subjected to a bending moment and a concentrated force at the free end and a uniformly-distributed load along the beam. The governing differential equations of the Timoshenko beam of a variable cross section are firstly derived from the principle of minimum potential energy. The differential equations are then solved to obtain the exact deflections and rotations along the beam. Formulas for computing the beam deflections and rotations at the free end are presented. Examples of application are given for the cases of a relatively slender beam and a deep beam. The present solutions can be useful for practical applications as well as for evaluating the accuracy of a numerical method.